Sugar, Acid Soluble Polysaccharide, and Total Phenolic Contents in Tropical Legumes and Their Relationships with In Vitro Nutrient Fermentability - A. Ikhwanti; A. Jayanegara; I. G. Permana; W. W. Wardani; Y. Retnani; A. A. Samsudin (Faculty of Animal Science, Bogor Agricultural University, 2020)
Tropical legume is a type of C4 plant that has been adaptive to hot environments. Therefore, tropical legumes require energy reserves in the form of sugar and starch. This study aimed to explain the relationship between sugar, starch, and tannin contents of tropical legumes and their in vitro fermentation profiles. Samples of Bauhinia purpurea, Pterocarpus indicus, Tamarindus indica, Calopogonium mucunoides, Macroptilium atropurpureum, and Stylosanthes guianensis were tested by proximate analysis, Van Soest, and in vitro nutrient fermentability. The in vitro fermentability consisted of dry matter degradability (DMD), organic matter degradability (OMD), volatile fatty acid (VFA), methane and ammonia concentrations, and gas production. The gas production kinetics were determined as gas production from soluble nutrient (a), maximum gas production (a+b), and rate of gas production (c). All samples were tested using the orthogonal contrast test to compare in vitro fermentability characteristics between the different types of legumes and their tannin contents. Results revealed that the average content of the legumes dry matter examined was 22% with CP content of 15% -28%. The legumes in this study had average content of 3.74% sugar, 21.86% ASP, and 0.3% total phenolics (dry matter basis). Acid soluble polysaccharides content in legumes had a positive correlation with degradability, ammonia concentration, and total gas production (p<0.05). However, sugar content did not have a correlation with the other in vitro fermentation characteristics. The exploration of sugar and acid soluble polysaccharides content in tropical legumes might be profitable as these nutrients could increase feeding efficiency. Sugar did not have a significant relationship to the characteristics of fermentation, on the contrary, acid soluble polysaccharides had a very close relationship to the characteristics of fermentation. The total phenolics had a close relationship with the production of VFA and ammonia. Tree legumes have better digestibility than shrub legumes.